Matrine Exerts Pharmacological Effects Through Multiple Signaling Pathways: A Comprehensive Review - Lin Y; He F; Wu L; Xu Y; Du Q (Dove Medical Press, 2022)
Yingda Lin,1,2,* Fuming He,2 Ling Wu,1 Yuan Xu,1 Qiu Du3,4,* 1Department of Pharmacy, the Affiliated Hospital of Yangzhou University, Yangzhou University, Yangzhou, 225012, People's Republic of China; 2Medical College, Yangzhou University, Yangzhou, 225001, People's Republic of China; 3Department of Neurosurgery, the Affiliated Hospital of Yangzhou University, Yangzhou University, Yangzhou, 225012, People's Republic of China; 4Department of Central Laboratory, the Affiliated Hospital of Yangzhou University, Yangzhou University, Yangzhou, 225012, People's Republic of China*These authors contributed equally to this workCorrespondence: Qiu Du, Department of Neurosurgery, the Affiliated Hospital of Yangzhou University, Yangzhou University, 368 Hanjiang Middle Road, Yangzhou, 225012, People's Republic of China, Email 092102@yzu.edu.cn Yuan Xu, Department of pharmacy, the Affiliated Hospital of Yangzhou University, Yangzhou University, 368 Hanjiang Middle Road, Yangzhou, 225012, People's Republic of China, Email feebyxuyuan@163.comAbstract: As The main effective monomer of the traditional Chinese medicine Sophora flavescens Ait, matrine has a broad scope of pharmacological activities such as anti-tumor, anti-inflammatory, analgesic, anti-fibrotic, anti-viral, anti-arrhythmia, and improving immune function. These actions explain its therapeutic effects in various types of tumors, cardiopathy, encephalomyelitis, allergic asthma, rheumatoid arthritis (RA), osteoporosis, and central nervous system (CNS) inflammation. Evidence has shown that the mechanism responsible for the pharmacological actions of matrine may be via the activation or inhibition of certain key molecules in several cellular signaling pathways including the phosphatidylinositol 3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR), transforming growth factor-β/mothers against decapentaplegic homolog (TGF-β/Smad), nuclear factor kappa B (NF-κB), Wnt (wingless/ integration 1)/β-catenin, mitogen-activated protein kinases (MAPKs), and Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathways. This review comprehensively summarizes recent studies on the pharmacological mechanisms of matrine to provide a theoretical basis for molecular targeted therapies and further development and utilization of matrine.Keywords: matrine, pharmacological effects, signaling pathways, review